Die Entwicklung des Pkw-Bestands in Deutschland - Michael Bräuninger; Mark-Oliver Teuber (Wirtschaftsdienst, 2023)
– The number of passenger cars in Germany has increased continuously in recent years and reached a new high of 48.8 million in 2023. This means that on average, there are 1.2 passenger cars for the 40.7 million households in Germany. On average, new registra-tions amount to 3.1 million vehicles per year over the past 10 years. The increase in passenger cars took place in almost all German dis-tricts and cities. Exceptions are regions with a strong population decline. The thesis that cars would become less important for mobility can be clearly rejected against the background of the present trends. There are two problems associated with the growing number of cars: On the one hand, CO2 emissions are associated with the operation of passenger cars. However, various upcoming regulations will impact this issue.. But another problem will remain: A large number of cars is accompanied by a high consumption parking space. To solve this problem, real prices must be charged for parking space.
Keywords: R22; R41; R11; 330; Fahrzeug; Kraftfahrzeug; Elektrofahrzeug; Hybridfahrzeug; Deutschland; Fahrzeug; Kraftfahrzeug; Elektrofahrzeug; Hybridfahrzeug; Deutschland